The Satisfaction Level of Early Childhood Educational Institutions On The Performance of Teachers As Graduates from Early Childhood Educational Study Program - Mukminin, Amirul; Waluyo, Edi; Diana, Diana (Universitas Negeri Semarang, 2019)
This study has a purpose to determine the satisfaction level of early childhood educational institutions on the performance of the teachers as alumni from early childhood educational program, to find out which competencies are considered to be the main aspirations by early childhood educational institutions in Central Java Province. This research has a target to get a complete overview about the satisfaction level of the institutions to the alumni as a chance to improve the quality of graduates from Early Childhood Educational Study Program of Faculty of Education in Semarang State University.The initial phase of the study, a survey was conducted at a number of Early Childhood Educational institutions spread across 35 cities and/or regencies in Central Java, to identify and find out whether there are graduates from Early Childhood Educational Study Program of Faculty of Education in Semarang State University who works as teacher at these institutions. In the second stage, the researchers did a mapping to determine which institutions will be used as research samples. The third phase of research was conducted to acquire understanding of the satisfaction level from the samples. The target which was aimed in this research is to develop curriculum in order to improve the quality of graduates. From the analysis result of the study, it showed that Early Childhood Educational institutions were satisfied with the performance of the graduates of Early Childhood Educational Study Program of Faculty of Education in Semarang State University which reached (58.41%). Early Childhood Educational institutions in Central Java would expect that the personality competence to be the first priority to be developed in the Early Childhood Educational Study Program in Semarang State University (36.84%), while the second priority is pedagogical competence (39.48%), professional competence (2.63%) becomes third priority and social competence (21.05%) become the last priority which need to be developed.